2011
DOI: 10.4161/trns.2.5.17272
|View full text |Cite
|
Sign up to set email alerts
|

The RNA polymerase C-terminal domain

Abstract: W ork over the last two decades has provided a wealth of data indicating that the RNA polymerase II transcriptional machinery can play an important role in facilitating the splicing of its transcripts. In particular, the C-terminal domain of the RNA polymerase II large subunit (CTD) is central in the coupling of transcription and splicing. While this has long been assumed to involve physical interactions between splicing factors and the CTD, few functional connections between the CTD and such factors have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…A key factor in this coordination is the CTD of the largest subunit of RNA polymerase II (234, 235). Phosphorylation of this CTD region is used to coordinate different stages in the transcription cycle, and the CTD interacts with a variety of proteins, including splicing factors.…”
Section: Connections To Other Rna Processing Reactionsmentioning
confidence: 99%
“…A key factor in this coordination is the CTD of the largest subunit of RNA polymerase II (234, 235). Phosphorylation of this CTD region is used to coordinate different stages in the transcription cycle, and the CTD interacts with a variety of proteins, including splicing factors.…”
Section: Connections To Other Rna Processing Reactionsmentioning
confidence: 99%
“…Interestingly, PGC-1 contains an RS domain that may function to recruit splicing factors to PCG-1-activated promoters. In the above and additional examples, the type of promoter-bound activator may influence splicing outcomes, in part by altering the composition and/or the processivity of Pol II (David and Manley, 2011). Understanding such effects therefore entails knowledge of factors that bridge activators and Pol II, and of components of Pol II that in turn transmit information to the nascent RNA to impact splicing.…”
Section: Integration Of Splicing With Chromatin and Transcriptionmentioning
confidence: 99%
“…Truncation to five repeats led to defects in capping, splicing, and 3′-end processing of model pre-mRNA reporters (McCracken et al, 1997b; McCracken et al, 1997a), and the CTD was later found to affect AS outcomes (de la Mata and Kornblihtt, 2006; Rosonina and Blencowe, 2004). The CTD promotes capping and 3′-end formation through direct interactions with sets of factors dedicated to these processes, and increasing evidence indicates that it also serves as a platform to recruit splicing factors that may participate in commitment complex formation and the regulation of AS (David and Manley, 2011; Hsin and Manley, 2012). …”
Section: Integration Of Splicing With Chromatin and Transcriptionmentioning
confidence: 99%
“…More recent work has identified a CTD-dependent splicing activity consisting of a complex containing U2AF65 and Prp19C 85 . U2AF65 binds directly to the CTD phosphorylated on both Ser2 and Ser5 85a .…”
Section: Functional Analysis Of Ctd Mutantsmentioning
confidence: 99%
“…U2AF65 binds directly to the CTD phosphorylated on both Ser2 and Ser5 85a . Transcripts produced from a CTD mutant in which Ser2 is substituted in all repeats with Ala is defective for splicing suggesting that this CTD phosphoisoform, present in the middle and 3’-end of genes is required for interaction with the splicosome 86 .…”
Section: Functional Analysis Of Ctd Mutantsmentioning
confidence: 99%